Communicating public avalanche warnings – what works? - R. V. Engeset; R. V. Engeset; R. V. Engeset; G. Pfuhl; M. Landrø; M. Landrø; M. Landrø; A. Mannberg; A. Mannberg; A. Hetland; A. Hetland (Natural Hazards and Earth System Sciences, 2018)
Like many other mountainous countries, Norway has experienced a rapid increase in both recreational winter activities and fatalities in avalanche terrain during the past few decades: during the decade 2008–2017, 64 recreational avalanche fatalities were recorded in Norway. This is a 106 % increase from that of the previous decade. In 2013, Norway therefore launched the National Avalanche Warning Service (NAWS), which provides avalanche warnings to transport and preparedness authorities and to the public. Previous studies suggest that avalanche warnings are used extensively in trip and preparedness planning and have a relatively strong influence on the decisions people make in order to reduce risk. However, no evaluation concerning how efficiently the warnings are communicated and understood has been done to date in Norway. Avalanche warnings communicate complex natural phenomena with a variable complexity and level of uncertainty about both the future and the present. In order to manage avalanche risk successfully, it is fundamental that the warning message can be understood and translated into practice by a wide range of different user groups. Users with little or no avalanche competence may need simple information to decide when to stay away from avalanche terrain, while professional users may need advanced technical details in order to make their decisions. To evaluate how different modes of communication are understood, and how efficiently the informational content is communicated, we designed and implemented a web-based user survey. The modes of presentation were based on the Varsom.no 2017 version (Varsom.no being the national portal for natural hazard warnings in Norway). We first used a panel of 110 experts from NAWS to answer the survey, and used their answers to establish the indented message of the avalanche warning. We thereafter received responses from 264 users and compared their answers to those of the NAWS experts for the different modes of communication. We developed a method, the comprehension effectiveness score, to test the comprehension. Our empirical analyses suggest that most users find the warning service to be useful and well suited to their needs. However, the effectiveness of a warnings seems to be influenced by the competency of the user and the complexity of the scenarios. We discuss the findings and make recommendations on how to improve communication of avalanche warnings.